Semen characteristics, extension, and cryopreservation of Rusa deer (Rusa timorensis) - Wan Jaafar, Wan Nor Fitri; Haron, Abd Wahid; Yusoff, Rosnina; Abdullah, Faez Firdaus Jesse; Zainal Abidin, Siti Aimi Sarah; Mohd Lila, Mohd Azmi; Che' Amat, Azlan; Rashid, Muhammad Azrolharith; Peter, Innocent Damudu; Baiee, Falah Hasan Ali (Veterinary World, 2017)
Aim: The objective of this research is to report parameters for breeding soundness evaluation, semen extension, and cryopreservation in Rusa timorensis. Materials and Methods: Seven healthy stags were chosen for semen collection using an electroejaculator. The collections were performed twice in a breeding season between February and June 2016. Samples were collected between 2 and 3 weeks interval, collected twice for each animal. Semen was evaluated, extended, and cryopreserved using four different extenders; Andromed®, BioXcell®, Triladyl®, and a modified Tris-egg yolk combined with Eurycoma longifolia Jack. Results: R. timorensis semen characteristics according to volume (ml), color, sperm concentration (106/ml), general motility (%), progressive motility (%), and % morphology of normal spermatozoa are 0.86±0.18 ml, thin milky to milky, 1194.2±346.1 106/ml, 82.9±2.8%, 76.1±4.8%, and 83.9±4.8%, respectively. Conclusion: Semen characteristics of R. timorensis collected by electroejaculation is good allowing for cryopreservation and future artificial insemination work. The most suitable extender for Rusa deer semen is Andromed®.